Evaluasi Penggunaan Fondasi Bore Pile Pada Bangunan Gedung Pelayanan Madrasah Aliyah Negeri Insan Cendekia Bengkulu Tengah - Reko Sopiyanto; Yudhia Pratidina Pestalozzi; Edito Dwi Antoro (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2023)
Based on data from the Bengkulu Province Bappeda, there were 3,341 buildings collapsed due to the failure of the lower structure (foundation). In the Service Building of Madrasah Aliyah Negeri Insan Cendekia, the foundation used can be considered inefficient. The reason is that the number of foundations is the same at each point even though each point has a different load and floor height. This study aims to evaluate the bearing capacity and the need for bore pile foundations in the Service Building of Madrasah Aliyah Negeri Insan Cendekia using quantitative methods. Based on the calculation of the ultimate bearing capacity (Qu) and allowable bearing capacity (Qizin) of the foundation, obtained (Qu) 208,992 tons, (Qizin) 65, 234 tons (Mayerhoof Method) and (Qu) 208,992 tons, (Qizin) 62,775 tons (Method Guy Sanglerat). The evaluation of the need for foundation piles using the Mayerhof method is the largest at the point of foundation one (P1) 3 foundation piles and the smallest is at the point of foundation five (P5) 1 pile foundation. Based on Guy Sanglerat's method, the largest foundation needs are at foundation points one and two (P1 and P2) 3 foundation piles, the smallest at foundation point five (P5) 1 foundation pile.